Initiating formulaic design to increase teachers professional development (TPD) for 21st Century teaching - Fardini Sabilah; Hilda Suat (Universitas Muhammadiyah Malang, 2020)
Encounter the changing needs of students in the 21st century of teaching and learning, English as a Foreign Language (EFL) teachers have to pursue professional development. EFL Teachers have to do this by assessing and reexamining their teaching preparation and practices. This study aimed to initiate a formulaic design to increase TPD for 21st-century teaching. The data were obtained through the open-form questionnaire with 20 English teachers, as well as through the unstructured interview. It was found that teachers still face difficulties dealing with 21st-century skills and Information and Communication Technology (ICT) Integration. Dual-mode of TPD could give a contribution as part of the training that is conducted in conventional ways, and the rest is delivered through the e-learning programs. A dual-mode TPD program as an initial model of TPD can be conducted both in conventional ways and through e-learning programs because it is the benefit to educate larger numbers of EFL teachers and more economically.